Evaluasi Kinerja Keuangan Bank Muamalat Indonesia Menggunakan Metode RGEC dan Islamicity Performance Index Periode 2016-2020 - Yulianti, Chika Dwi Rahma; Wahyuni, Eka Sri; Hariyadi, Rizky (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2022)
This study aims to determine the financial performance of Bank Muamalat Indonesia (BMI) for the 2016-2020 period. The study used descriptive quantitative methods. Evaluation of the financial performance of Bank Muamalat Indonesia (BMI) is carried out using the REGC method and the Islamicity Performance Index method. The results of the assessment of the financial performance of Bank Muamalat Indonesia (BMI) using the REC (Risk Profile, Earnings, and Capital) method can be concluded that the performance of Bank Muamalat Indonesia (BMI) for the 2016-2020 period is in good condition. The results of the evaluation of sharia financial performance based on the Islamicity Performance Index show that the sharia performance of Bank Muamalat Indonesia (BMI) for the 2016-2020 period is in poor condition, but BMI is the first Islamic bank and is still a bank that has made efforts to implement sharia principles and its social obligations as an Islamic bank.